Non-occlusive intestinal ischemia in the ascending colon and rectum: a pediatric case occurring during encephalitis treatment - Noboru Oyachi; Takaki Emura; Fuminori Numano; Tomoko Tando; Tomohiro Saito; Yusuke Goto (Surgical Case Reports, 2019)
Abstract Background Non-occlusive mesenteric ischemia (NOMI) is a rare and severe pathological condition that can cause intestinal necrosis without mechanical obstruction of the mesenteric artery. NOMI often develops during the treatment of severe disease in elderly patients and mostly occurs in the intestine supplied by the superior mesenteric artery (SMA). We experienced a 12-year-old patient with NOMI that was segmentally localized in the ascending colon and rectum during encephalitis treatment. Case presentation A 12-year-old boy was hospitalized with limbic encephalitis. On day 41 after admission, he abruptly developed hypotension following diarrhea and fever, and presented abdominal distension. A computed tomography scan revealed pneumatosis intestinalis localized in the ascending colon and rectum coexisting with portal venous gas. The presence of peritoneal signs required an emergency laparotomy. Intraoperatively, skip ischemic lesions were found in the ascending colon and the rectum without bowel perforation. SMA and superior rectal arterial pulsation were present, and the patient was diagnosed with NOMI. The remaining colon, from the transverse to the sigmoid colon, appeared intact. We performed a distal ileostomy without bowel resection. Postoperative colonoscopies were carried out and revealed rectal and ascending colon stenosis with ulceration but demonstrated the patency of the two lesions. We confirmed the improvement of the transient bowel strictures; therefore, the ileal stoma was closed 14 months after the previous laparotomy. Conclusion NOMI can be present in childhood during encephalitis treatment and can be segmentally localized in the ascending colon and the rectum. Although NOMI is most often seen in elderly patients, we should also consider the possibility of NOMI when pediatric patients with severe illness manifest abdominal symptoms.